Examining the Impact of Marketing Capability Innovation on International Investment Performance with the Mediating Role of Behavioral Marketing Communications and the Moderating Effect of Technological Turbulence - Moghadamnia, Elham (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this study is to examine the impact of marketing capability innovation on international investment performance with the mediating role of marketing communications and the moderating effect of technological turbulence. Method: In terms of objective, this research is applied and is categorized as survey research since it utilizes field data for testing hypotheses. The study population consists of board members, managers, and deputy managers of the Mapna Group companies, totaling about 240 individuals. A sample size of 144 was obtained using Morgan’s table, and a simple random sampling method was employed. To measure research variables, a standard questionnaire was used, which was deemed to have suitable validity, and the reliability of the questionnaires was confirmed through Cronbach’s alpha. This research utilized structural equation modeling approach and PLS software for data analysis. Findings: The results indicated that marketing capability innovation positively and significantly affects competitive strategy, export investment performance, and behavioral marketing communications. Moreover, competitive strategy has a positive and significant impact on export investment performance. On the other hand, behavioral marketing communications significantly influence export investment performance and also mediate between competitive strategy and export investment performance. Conclusion: Finally, the results showed that technological turbulence plays a moderating role between marketing capability innovation and behavioral marketing communications, as well as between marketing strategy and behavioral marketing communications.